Quantitative bounds for the $U^4$-inverse theorem over low characteristic finite fields - Jonathan Tidor (Discrete Analysis, 2022)
Quantitative bounds for the $U^4$-inverse theorem over low characteristic finite fields, Discrete Analysis 2022:14, 17 pp.